2020
DOI: 10.1038/s42005-020-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a motility-trap for active particles

Abstract: Trapping of atomic and mesoscopic particles with optical fields is a practical technique employed in many research disciplines. Developing similar trapping methods for self-propelled, i.e. active, particles is, however, challenging due to the typical anisotropic material composition of Janus-type active particles. This renders their trapping with magneto-optical fields to be difficult. Here we present the realization of a motility-trap for active particles, which only exploits their self-propulsion properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…We fix k = 5/4 to consider a regime of the persistence length large if compared with the spatial period of u(x). The two relaxation times, in the long-time regime and in the small-time one, do not depend on a, in agreement with prediction (21). However, a affects the survival time of the small time-regime, so that larger values of a (close to the maximal value 1) mean that C vv (t) reaches very small values already in the first time regime, approaching zero for a = 1.…”
Section: Velocity Autocorrelation Functionsupporting
confidence: 88%
See 3 more Smart Citations
“…We fix k = 5/4 to consider a regime of the persistence length large if compared with the spatial period of u(x). The two relaxation times, in the long-time regime and in the small-time one, do not depend on a, in agreement with prediction (21). However, a affects the survival time of the small time-regime, so that larger values of a (close to the maximal value 1) mean that C vv (t) reaches very small values already in the first time regime, approaching zero for a = 1.…”
Section: Velocity Autocorrelation Functionsupporting
confidence: 88%
“…As shown in Fig. 4(a), the profile (21) fairly agrees with numerical simulations after a transient time which depends on the value of k. Moreover, for k { 1, the persistence length is much smaller than S and the particle velocity relaxes before the spatial variation of the swim velocity affects the dynamics of the system and we can again neglect @ @x uðxÞ in eqn (20) to recover the approximation for C vv (t) given by eqn (21) (see the black dashed curve in Fig. 4(b)).…”
Section: Velocity Autocorrelation Functionsupporting
confidence: 76%
See 2 more Smart Citations
“…This phenomenon has been termed "chemotaxis in a non-biological colloidal systems". More recently it has also been observed that some Janus-colloids show "artificial" phototaxis and respond to external light gradients [124][125][126][127][128] as well as thermotaxis [129][130][131]) and rheotaxis [132][133][134][135].…”
Section: Measurementsmentioning
confidence: 99%